ORGANOLEPTIC TEST OF CHICKEN MEATBALLS WITH WHITE TOFU SUBSTITUTION AT DIFFERENT CONCENTRATIONS - Fitri Dian Nilasari; Siti Nurlani Harahap (INJOSEDU: International Journal of Social and Education, 2026)
Meatballs are a processed meat product that is well-known and loved by the public. Meatballs are one of the food products regulated by the Indonesian National Standard (SNI). One parameter for determining whether a meatball product is good or not is its elasticity. People tend to prefer meatballs with a chewy texture and not hard. Factors that influence meatball texture are the composition of the meatball, the manufacturing process, and the heating time. The purpose of this study was to determine whether the addition of white tofu can affect the quality of chicken meatballs and to determine the best percentage of white tofu in making meatballs so that it can substitute the use of chicken. This study used different percentages of white tofu, namely 25%, 50%, 75%, and 100%. Organoleptic tests were carried out on taste, color, texture, and aroma. Data were analyzed using one-way ANOVA followed by the Duncan test. The best treatment with the highest average results in making chicken meatballs with white tofu substitution for organoleptic quality based on taste, color, texture, and aroma was in the control treatment P1 with the addition of 0% white tofu with an average score of 3.9 which was in the very like category, followed by P2 with the addition of 25% white tofu with an average score of 3.4667 which was in the like category.